AC plasma induced modifications in Sb2S3thin films - Calixto Rodriguez, María Estela; Castillo, F.; Martínez, Heriberto; Peña Méndez, Yolanda; Sánchez Juárez, Arón (2010)
Sb2S3 thin films, deposited by the chemical bath deposition method, were treated with N2 plasma at 3.0 Torr during several minutes. The as-prepared Sb2S3 thin films and films treated with N2 plasma have been characterized using several techniques. X-ray diffraction studies have shown that plasma treatment induced recrystallization on the as-prepared Sb2S3 thin films. The band gap values decreased from 2.37 to 1.82 eV after plasma treatment, and the electrical conductivity increased from 10 to 10 ( cm) due to the annealing effect.